Working Relationship Between Police Functional Units in Disclosing Motorbike Gangs Committing Crimes in the Jurisdiction of Medan Helvetia Police Sector - Gilang Gemilang; Sumarno Sumarno; Suci Ramadhani (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The police are a civil public intermediary that regulates order and law. Police officers as state servants must uphold humanitarian values ​​and be an example for society. As stated in the oath and promise of members of the Indonesian National Police. This is stated in the opening of the code of ethics of the Indonesian National Police profession. According to Law Number 2 of 2002 concerning the Indonesian National Police. The function of the police is one of the functions of the state government in the field of maintaining public security and order, law enforcement, protection, shelter, and service to the community. The problem raised is the working relationship between police function units in disclosing criminal acts at the Medan Helvetia Police. The method used in discussing the formulation of the problem is normative legal research. Normative legal research is an approach carried out based on primary legal materials by examining theories, concepts, legal principles and laws and regulations related to this research. The working relationship between the police functional units in disclosing criminal acts at the Medan Helvetia Police, namely starting from the SPKT Unit of the Medan Helvetia Police coordinating with the police functional units at the Medan Helvetia Police to conduct a crime scene check (TKP); the Samapta Unit carries out security around the house object; the Intelkam Unit conducts an investigation into the case, collects information or (Pulbaket); the Criminal Investigation Unit conducts an in-depth investigation at the crime scene; the Traffic Unit regulates traffic around the crime scene; the Binmas Unit coordinates with the Head of the Environment and local sub-district and the Samapta Unit of the Medan Helvetia Police carries out patrols in the area. Meanwhile, the factors that hinder the working relationship between the police functional units in disclosing criminal acts at the Medan Helvetia Police are external factors such as the lack of public knowledge of the importance of handling the crime scene (TKP); time factors; weather factors. While internal factors consist of being less careful or careless towards an object; lack of facilities and infrastructure for officers; quality of identification officers; facilities and infrastructure.